TAX RISK MANAGEMENT STRATEGIES FOR MULTINATIONAL COMPANIES - Loso Judijanto; Teti Anggita Safitri; Era Purike; Fuadah Johari (INJOSEDU: International Journal of Social and Education, 2025)
Tax risk management is a central aspect for multinational companies operating in multiple jurisdictions with diverse tax regulations. The key to meeting this challenge is the implementation of a comprehensive and integrated risk management strategy. Key challenges include internal resistance to change, the need for cross-departmental coordination, and global communication issues. In addition, non-uniformity in tax monitoring and reporting can increase the risk of non-compliance, which in turn can potentially lead to legal sanctions. To overcome these challenges, companies need to focus on continuous training and skills development for employees. Investment in technology that supports tax risk management is also central, including data analysis tools and solid audit systems. Ensuring cross-departmental integration and efficient communication can help support a collaborative approach to tax risk management, strengthen transparency, and improve accuracy in tax reporting. The implication of this strategy is that multinational companies can minimise tax management risks and mitigate potential adverse legal sanctions. With the systematic adoption of such strategies, companies not only maintain compliance with tax regulations, but also strengthen their position in an increasingly competitive global business climate. Thus, an effective tax risk management strategy can be one of the critical pillars in the long-term success of multinational companies.